Kepemimpinan Simbiotik antara Manusia dan Kecerdasan Buatan: Rekonstruksi Peran Pemimpin dalam Organisasi Berbasis Algoritma - Nuri Shafi Alya; Muhammad Adib Auladi; Widya Permata Sari; Mochammad Isa Anshori (Pusat Riset dan Inovasi Nasional, 2026)
Digital transformation driven by the advancement of Artificial Intelligence (AI) has significantly reshaped leadership dynamics in modern organizations, particularly in algorithm-based decision-making processes. This study aims to analyze and formulate the concept of symbiotic leadership between humans and AI as an adaptive leadership model in the digital era. The research employs a Systematic Literature Review (SLR) method by examining reputable academic articles published within the last five years that are relevant to leadership and technology. The findings indicate that leadership is shifting from a traditional role as a sole decision-maker to a facilitator of collaboration between humans and AI systems, emphasizing the integration of technological analytical capabilities with human contextual and ethical judgment. Furthermore, leadership effectiveness in algorithm-based organizations is strongly influenced by digital literacy, adaptability, and the ability to manage issues related to ethics, transparency, and trust. Therefore, symbiotic leadership emerges as a relevant approach to bridge the gap between technological advancement and human-centered needs in modern organizations. Overall this perspective reinforces the importance of balancing innovation with responsibility while ensuring that human values remain central in decision-making processes supported by intelligent systems in contemporary organizational contexts and sustainable future development goals across industries globally today in practice effectively.